A population genomics appraisal suggests independent dispersals for bitter and sweet manioc in Brazilian Amazonia. (19th October 2019) - Alves‐Pereira, Alessandro; Clement, Charles R.; Picanço‐Rodrigues, Doriane; Veasey, Elizabeth Ann; Dequigiovanni, Gabriel; Ramos, Santiago Linorio Ferreyra; Pinheiro, José Baldin; de Souza, Anete Pereira; Zucchi, Maria Imaculada
Abstract: Amazonia is a major world centre of plant domestication, but the genetics of domestication remains unclear for most Amazonian crops. Manioc ( Manihot esculenta ) is the most important staple food crop that originated in this region. Although manioc is relatively well‐studied, little is known about the diversification of bitter and sweet landraces and how they were dispersed across Amazonia. We evaluated single nucleotide polymorphisms (SNPs) in wild and cultivated manioc to identify outlier SNPs putatively under selection and to assess the neutral genetic structure of landraces to make inferences about the evolution of the crop in Amazonia. Some outlier SNPs were in putative manioc genes possibly related to plant architecture, transcriptional regulation and responses to stress. The neutral SNPs revealed contrasting genetic structuring for bitter and sweet landraces. The outlier SNPs may be signatures of the genomic changes resulting from domestication, while the neutral genetic structure suggests independent dispersals for sweet and bitter manioc, possibly related to the earlier domestication and diversification of the former. Our results highlight the role of ancient peoples and current smallholders in the management and conservation of manioc genetic diversity, including putative genes and specific genetic resources with adaptive potential in the context of climate change.